Infant respiratory infections modulate lymphocyte homing to breast milk - Zheng, Yingying; Corrêa-Silva, Simone; Rodrigues, Regina Maria; Corrêa de Souza, Eloisa; Macaferri da Fonseca, Fernanda A.; Gilio, Alfredo Elias; Carneiro-Sampaio, Magda; Palmeira, Patricia (Frontiers in Immunology, 2025)
IntroductionChemokines and their receptors are essential for leukocyte migration to several tissues, including human milk. Here, we evaluated the homing of T and B lymphocyte subsets to breast milk in response to ongoing respiratory infections in the nursing infant.MethodsBlood and mature milk were collected from healthy mothers of nurslings with respiratory infections (Group I) and from healthy mothers of healthy nurslings (Group C). Total lymphocyte, T and B cells, their subset numbers, and the expression of the homing receptors CCR5, CCR6, CCR10, and CXCR3 in these cells were evaluated in milk. Maternal serum and milk chemokine, cytokine, and IgA and IgG antibody levels were also quantified.ResultsAll milk lymphocyte numbers were greater in Group I than in Group C. All CD4 T-cell subsets expressing CCR5, CCR6, and CXCR3 were higher in Group I. Within the CD8 T-cell subsets, only CCR6 and CXCR3 were higher in Group I, while CCR5 expression was higher in Group I exclusively for activated CD8 T cells. Group I showed greater numbers of all CCR6+ B-cell subsets and CXCR3+ naive B cells and plasma cells than did Group C. Infection of the nurslings promoted increased CCL20, CXCL10, IL-6, IL-8, total IgA, and IgG levels in the milk.ConclusionRespiratory infections in nursing infants stimulate an increase in cytokines and chemokines in breast milk, facilitating the recruitment and activation of lymphocytes. This process may promote immunological tolerance and help in the maturation of the infant's immune system, providing an additional strategy for passive maternal-infant protection.